Pengaruh Penerapan Metode Applied Behavior Analysis (ABA) pada Anak Penyandang Autisme - Fredeswinda Rara Widaranti Langga; Eva Pravitasari Nefertiti; Sitti Radhiah; Wahyu Prasasti Mutiadesi (Universitas Ciputra Surabaya, 2023)
Autism or autism spectrum disorder (ASD) is a neurodevelopmental disorder characterized by deficit in social communication and interaction with restricted and repetitive behavior, interest, or activities. The Applied Behavior Analysis (ABA) method is a behavioral approach that has the possibility of improving clinical manifestations in the aspects of social communication and interaction with the behavior of children with autism. This study aims to determine the effect of applying the ABA method in children with autism. This study used a literature review from 20 national journals indexed by SINTA or Garuda and international journals indexed by Scopus or Scimago in the last 5 years, from 2017 to 2022. The results of the journal review conducted found that the application of the ABA method has significant effectiveness in improving various kinds of clinical manifestations in aspects of impaired social communication and interaction with restricted and repetitive behavior in children with autism. This study concludes that the application of the ABA method affects social communication and interaction with the behavior of children with autism.